Critical Discourse Analysis of Abortion Article on Law on Health and Government Regulation of Reproductive Health - Anita Dhewy (Yayasan Jurnal Perempuan, 2017)
Abortion in Indonesia is a prohibited act, as regulated in Law no. 36 of 2009 on Health and Government Regulation no. 23 of 2014 on Reproductive Health. However, in that provision there are exceptions based on medical emergency indications and pregnancy due to rape. By using critical discourse analysis from Fairclough, this research attempts to dismantle social irregularities related to the prohibition of abortion on both rules. The results of the analysis show that exceptions to the ban on abortion are not really in favor of women. Therefore, fundamental changes related to the paradigm of rights and reproductive health and the paradigm of abortion are needed.